Surah Al-Nisa’: Some Lessons for Muslim Business Leaders Based on the Works of Khaled and Khan (Surah Al-Nisa’: Beberapa pelajaran untuk Pemimpin Perniagaan Muslim berdasarkan Tafsiran Khaled dan Khan) - Fontaine, Rodrigue (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
This study looks at sūrah al-Nisa’ (Chapter The Women) and draws some lessons for Muslim business leaders. The focus is on Muslim business leaders as they have the power and authority to transform the corporate culture of their organisations. The author compared and contrasted the works of Khaled and Khan. Although the general theme of the sūrah is justice, this author focuses on ihsan. Generally, people need to have ihsan towards one another (4:36), whether Muslims or non-Muslims. Extrapolating from this principle, this sūrah teaches us that managers need to have ihsan towards their subordinates and vice-versa. The complexity of the concept of ihsan is explored. Although ihsan is linked to taqwa (piety), it is also linked to remembering death and resurrection. The author tried two experiments, derived from the work of Kübler-Ross, to demonstrate how developing a culture of ihsan is possible. The findings state that developing a culture of ihsan is straightforward but facilitators need to have a counselling background to address participants’ concerns in the right manner. Keywords: Qur’an, ihsan, corporate culture, counselling, Islamic leadership. Abstrak Kajian ini tentang sūrah an-Nisa bagi mengambil beberapa pengajaran untuk pemimpin perniaga Islam. Tumpuannya khusus pemimpin perniaga Islam kerana mereka mempunyai kuasa dan autoriti untuk mengubah budaya korporat organisasi mereka. Penulis membandingkan dan membezakan karya-karya Khaled dan Khan. Walaupun tema umum sūrah ini adalah keadilan tetapi penulis memberi tumpuan tentang konsep ihsan. Secara umum, setiap orang perlu mempunyai ihsan terhadap satu sama lain (4:36), sama ada orang Islam atau bukan Islam. Pengkaitan daripada prinsip tersebut, sūrah ini mengajar kita bahawa pengurus perlu mempunyai ihsan kepada orang bawahan mereka dan sebaliknya. Konsep ihsan yang menyeluruh dan berhubung kait juga diteroka. Walaupun ihsan dikaitkan dengan taqwa (taqwa), ia juga dikaitkan dengan mengingati kematian dan kebangkitan. Penulis melakukan dua eksperimen, yang berasal dari karya Kübler-Ross, untuk menunjukkan keupayan membangunkan budaya ihsan. Kesimpulannya ialah membina budaya ihsan adalah mudah tetapi memerlukan fasilitator yang mempunyai latar belakang kaunseling untuk menangani masalah peserta dengan cara yang berkesan. Kata Kunci: Al-Qur’an, ihsan, budaya korporat, kaunseling, kepimpinan Islam.